Optimization-Based Layout Design - K. Abdel-Malek; Z. Mi; J. Yang; K. Nebel (Applied Bionics and Biomechanics)
The layout problem is of importance to ergonomists, vehicle/cockpit packaging engineers, designers of manufacturing assembly lines, designers concerned with the placement of levers, knobs, controls, etc. in the reachable workspace of a human, and also to users of digital human modeling code, where digital prototyping has become a valuable tool. This paper proposes a hybrid optimization method (gradient-based optimization and simulated annealing) to obtain the layout design. We implemented the proposed algorithm for a project at Oral-B Laboratories, where a manufacturing cell involves an operator who handles three objects, some with the left hand, others with the right hand.